2015
DOI: 10.1371/journal.pone.0136184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracuff Lidocaine on Postoperative Sore Throat and the Emergence Phenomenon: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundPostoperative sore throat and other airway morbidities are common and troublesome after endotracheal tube intubation general anesthesia (ETGA). We propose lidocaine as endotracheal tube (ETT) cuff inflation media to reduce the postintubation-related emergence phenomenon.MethodsWe searched PubMed, EMBASE, and Cochrane databases systematically for randomized controlled trials (RCTs) that have investigated the outcome of intracuff lidocaine versus air or saline in patients receiving ETGA. Using a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 47 publications
1
38
0
6
Order By: Relevance
“…Lidocaine within tracheal tube cuffs seems to exert a localised effect on the trachea after diffusing through the cuff, resulting in improved tolerance to tracheal and tracheostomy tubes. A recent systematic review and meta‐analysis showed that both alkalinised and non‐alkalinised lidocaine used to fill tracheal tube cuffs reduce the incidence of postoperative sore throat . In addition, it has been shown that lidocaine minimises haemodynamic changes during tracheal extubation in adults .…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine within tracheal tube cuffs seems to exert a localised effect on the trachea after diffusing through the cuff, resulting in improved tolerance to tracheal and tracheostomy tubes. A recent systematic review and meta‐analysis showed that both alkalinised and non‐alkalinised lidocaine used to fill tracheal tube cuffs reduce the incidence of postoperative sore throat . In addition, it has been shown that lidocaine minimises haemodynamic changes during tracheal extubation in adults .…”
Section: Discussionmentioning
confidence: 99%
“…Cough-preventing strategies have been proposed, such as "deep extubation," 11,12 gargling with various substances, 13 or topical or intracuff lidocaine. 14 The clinical relevance of intravenous (IV) lidocaine as a way to blunt cough during tracheal intubation is deserved by specific and challenging clinical circumstances where avoidance of neuromuscular blocking agents is recommended or even mandatory. These conditions could include, for instance, awake intubation for expected difficult airway management, airway obstruction in children, known severe allergy to neuromuscular blocking agents, or certain neuromuscular disorders (eg, myasthenia gravis).…”
mentioning
confidence: 99%
“…Fai Lam et al 21 in their systematic review and meta-analysis of randomized control trials evaluating intracuff alkaline lignocaine in endotracheal tube in 2009 concluded the effectiveness of intracuff lignocaine used in the prevention of emergence phenomenon. Navarro et al 22 in their study conducted in 2012 evaluated 50 smoking patients comparing intracuff alkaline lignocaine and saline and demonstrated decreasing the incidence of emergence coughing and sore throat during the postoperative period in smokers. This study was conducted in a group with high airway reflexivity to chemical and mechanical stimulations.…”
Section: Discussionmentioning
confidence: 99%